2007
DOI: 10.1159/000099012
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Acute Renal Failure in Patients Hospitalized for Decompensated Congestive Heart Failure

Abstract: Introduction: Congestive heart failure (CHF) is an important cause of hospital admissions and is associated with an increased risk for development of acute renal failure (ARF). The purpose of this study was to describe the incidence of ARF, to ascertain risk factors for its development, and to determine whether ARF impacts hospital outcomes. Methods: Review was conducted of 509 hospital medical records of patients hospitalized with a principal diagnosis of CHF during 2004. ARF was defined as an increase in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 33 publications
3
40
0
3
Order By: Relevance
“…attention has recently been paid to the interaction between the heart and kidney, termed cardiorenal syndrome, because of its association with adverse outcomes [1][2][3]. Several studies have suggested that worsening of renal function during aDHF therapy is one of the most powerful predictors of mortality [4][5][6][7][8][9]. However, after the exclusion of several biases, an increase in serum creatinine level has been shown to have little impact on mortality in patients with aDHF [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…attention has recently been paid to the interaction between the heart and kidney, termed cardiorenal syndrome, because of its association with adverse outcomes [1][2][3]. Several studies have suggested that worsening of renal function during aDHF therapy is one of the most powerful predictors of mortality [4][5][6][7][8][9]. However, after the exclusion of several biases, an increase in serum creatinine level has been shown to have little impact on mortality in patients with aDHF [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…From an economical point of view, these outcomes result in a continuously growing burden on in-hospital and posthospitalization resources [17], demanding a new preventive and therapeutic approach. Identification of new risk factors, such as the presence of anemia at hospital admission, in addition to the further investigation of well-established risk factors [18,19,20,21,22,23,24,25,26], is essential for AKI prevention [18]. …”
Section: Discussionmentioning
confidence: 99%
“…An increase in serum creatinine level is observed in 21-45% of patients admitted with acute decompensated HF (74)(75)(76)(77). Activation of RAAS and SNS due to reduced cardiac output volume and the effects of increased intraabdominal pressure (IAB) on the kidney are thought to be the causative mechanisms (24).…”
Section: How Does Peritoneal Dialysis Affect Glomerular Filtration Rate?mentioning
confidence: 99%